Secret to Finlands Education Success: A Reflection for Education in Indonesia - Moch. Said Mardjuki; Sihab Lapoto Ade Potradinata (Universitas Muhammadiyah Semarang, 2017)
Finland has emerged as the top-scoring of Organization for Economic Cooperation and Development (OECD) on theProgram of International Student Achievement (PISA) assessment since 2000. Its secondary school students regularly achieve high scores in PISA tests.Finland has one of the worlds best performing education systems.The gap between the highest and lowest students within schools is not significant.Many researches have been conducted by researchers from various countries to investigate the Finlands education success.As a developing country, Indonesia is one of the lowest-scoring OECD nation on PISA. Finlands education could be a model for Indonesia. This study is aimed to present the secret of Finlands education success and to compare with Indonesian educational system. Based on the analysis, the most probable factors as the key elements that has impacted Finlands education success are excellent teachers, and appropriate curriculum and educational system. The writers try to propose solutions for Indonesian teachers and Indonesian educational system policy makers to be used as a reference.